Conflict management in digital business : new strategy and approach - Özsungur, Fahri, 1981- (Emerald Publishing, 2022)
Providing readers with a unique guide of how businesses can achieve resilience to digital conflict, Conflict Management in Digital Businesshelps prepare for unexpected situations such as pandemics, to maintain competitive advantage, and illuminating pathways to turn conflicts caused by extraordinary situations into opportunities.- Resumé vydavatel